2001
DOI: 10.1021/bc0001185
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Linked Liposomal Antigen Induces IgE-Selective Unresponsiveness Regardless of the Lipid Components of Liposomes

Abstract: We have previously reported that antigen coupled with liposomes induced antigen-specific and IgE-selective unresponsiveness in mice. This antigen preparation was investigated for application in a novel vaccine protocol to induce minimal IgE synthesis. In this study, ovalbumin (OVA)-liposome conjugates were made using liposomes of four different lipid components, including unsaturated carrier lipid and three different saturated carrier lipids, after which the induction of anti-OVA antibody production was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 15 publications
(17 reference statements)
4
47
3
Order By: Relevance
“…The oleoyl liposomes consisted of dioleoyl phosphatidylcholine, dioleoyl phosphatidylethanolamine, dioleoyl phosphatidylglycerol acid, and cholesterol in a 4:3:2:7 molar ratio (29). Each peptide was coupled to the surfaces of the liposomes by the use of disuccinimidyl suberate, as described previously (42).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oleoyl liposomes consisted of dioleoyl phosphatidylcholine, dioleoyl phosphatidylethanolamine, dioleoyl phosphatidylglycerol acid, and cholesterol in a 4:3:2:7 molar ratio (29). Each peptide was coupled to the surfaces of the liposomes by the use of disuccinimidyl suberate, as described previously (42).…”
Section: Methodsmentioning
confidence: 99%
“…The inducibility of Ag-specific IgG production was found to vary among liposome preparations: the greater that the membrane mobility in the liposomes is, the greater that the antibody production induced by Ag-liposome conjugates is (29). In our previous study, we have reported that ovalbumin (OVA) coupled to liposomes made with unsaturated fatty acids was presented to both CD4 ϩ and CD8…”
mentioning
confidence: 99%
“…2). The results suggest that the membrane fluidity of liposomes might affect the adjuvant effect of liposomes but not the induction of IgE-selective unresponsiveness in immunizations with surface-linked liposomal antigens (16).…”
Section: Introductionmentioning
confidence: 91%
“…By contrast, intramuscularly injected fluid-state liposomes are rapidly removed, do not appear to stimulate positive costimulation, and are much less capable of stimulating a T cell response [28]. Whether the intramuscular fluid liposome-antigen combination induced peripheral immune tolerance was not tested, but intraperitoneal (IP) administration of fluid OVA-decorated liposomes can induce antigen-specific IgE non-responsiveness [31,32]. While this was argued to occur in a T cell-independent fashion, the increased levels of IgG after IP administration suggest immune deviation [33].…”
Section: Stiffness and Fluiditymentioning
confidence: 99%